Implementing Integrative Nursing in a Pediatric Setting - Megan E. Voss; Mary Jo Kreitzer (MDPI AG, 2018)
Pediatric blood and marrow transplantation (BMT) is one of the most challenging allopathic treatments a patient and family can be faced with. A large Midwest academic health center, and leader in pediatric BMT, made the decision in 2013 to incorporate integrative nursing as the care delivery model. Nurses trained in advanced nursing practice and specialized in integrative health and healing performed a deep-dive needs assessment, national benchmarking, a comprehensive review of the literature, and ultimately designed a comprehensive integrative program for pediatric patients and their families undergoing BMT. Four years after implementation, this paper discusses lessons learned, strengths, challenges and next phases of the program, including a research agenda. The authors conclude that it is feasible, acceptable and sustainable to implement a nurse-led integrative program within an academic health center-based pediatric BMT program.